Efeitos da maternidade e do casamento sobre o diferencial de salários entre gêneros no Brasil para o ano de 2014 - Souza, Paola Faria Lucas de (2016)
This thesis relates motherhood and marriage with salary. The database used is the PNAD of 2014. There are three chapters. In the first, it is made an analysis of the motherhood role in women's wage differentials. The main contribution is to place Brazil in the literature of motherhood pay gap, emphasizing mainly that the effects of maternity should exclude differences of productive characteristics between mothers and non mothers. Four regressionn specificantions and the Oaxaca-Blinder decomposition were used, both with correction for selection bias and considering adaptations to complex databases. Main results: i) salary penalties for mothers; ii) increase in the wage penalty with the number of children; (iii) stabilization of the penalty from the third child; iv) wage difference due to maternity similar to that found for genders; v) maternal characteristics as a determinant of lower wages, vi) lower effect of maternity on wages for mothers in typical male activities. In the second chapter analysis of the motherhood pay gap for all salary distribution, conditional and unconditional. In order to analyze conditional effects, quantitative regressions are adopted, whereas for the unconditional analysis it is used the decomposition of Melly (2006). The innovations are to make quantile study, selection bias correction in both techniques following an adaptation of Buchisky (2001), and adopt the decomposition of Melly (2006) to measure the motherhood pay gap. Main results: i) the greater maternity penalty is in the highest conditional quantiles; ii) the higher the number of children leave higher wage penalty in all the conditional deciles; iii) the wage gap due to maternity increases with the level of income; iv) most of the wage gap is not explained by differences in attributes between groups. In the third chapter it is argued that marriage generates a wage premium for men and a wage penalty for women, what can increase the gender pay differentials. This behavior is shown for the wage distribution. The methodologies used were: decomposition of the T-Theil index, unconditional quantile regressions (by RIF) and the decompositions of Oaxaca-Blinder (1973) and Firpo, Fortin and Lemieux (2009). Main results: i) there is a marriage wage premium for men; ii) there is a matrimonial salary penalty for women; iii) the division of domestic labor does not justify higher incomes for men; iv) there are indications of differential wage treatment for single men and married women in the labor market; v) the wage penalty of marriage for women is higher for those with higher incomes; vi) salary bonuses are higher for men with higher incomes; (vii) single marital status is the worst in terms of wages for men; (viii) married marital status is the worst in terms of wages for women.